The comedia of virginity : Mary and the politics of seventeenth-century Spanish theater - Pérez, Mirzam C., 1967- (Baylor University Press, 2012)
"Analyzes the social, political, and theological implications of the Virgin Mary in three early modern plays from Hapsburg, Spain"--